Geomorphological risks and assessment of ecological-geomorphological situations of mining regions of arid zone of Kazakhstan - Roza Bexeitova (Vilnius Gediminas Technical University, 2021)
The importance of the impact of emerging ecologic-geomorphological situations in areas of active mining development of Kazakhstan on the life of the population is difficult to overestimate in conditions of a dry climate, water scarcity and the use of outdated technologies for the extraction of solid minerals. This article examines the ecologic-geomorphological situations of mining areas of arid platform-denudation plains of Kazakhstan and gives their characteristics, which is based on an analysis of the leading natural and anthropogenically caused geodynamic processes, their spatial coverage, ratios and comparative assessment as an indicator of geomorphological risk within selected morphogenetic types of relief.